2003
DOI: 10.1128/jvi.77.11.6178-6187.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Stress-Inducible Immediate-Early Responsive Gene IEX-1 Is Activated in Cells Infected with Herpes Simplex Virus 1, but Several Viral Mechanisms, Including 3′ Degradation of Its RNA, Preclude Expression of the Gene

Abstract: The accumulation of cellular transcripts from cells infected with herpes simplex virus 1 (HSV-1) as measured with the aid of Affymetrix microchips has been reported elsewhere. Among these transcripts were genes that respond to stress and that could have a noxious effect on viral replication. We have selected the stress-inducible cellular gene encoding the immediate-early response protein IEX-1 to verify and determine the significance of the accumulation of these transcripts in infected cells. We report that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
73
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(87 citation statements)
references
References 30 publications
8
73
6
Order By: Relevance
“…The results described above were in agreement with the pattern of degradation of IEX-1 mRNA observed in HSV-1-infected cells and specifically with the lingering of truncated 5Ј domains, generated by vhs-dependent endonucleolytic cleavage within the AREs (19,21). The objective of the experiments described in this section was to test whether a substrate, consisting of only IEX-1 coding sequence domain (CDS, substrate 3), was cleaved by the purified GST-vhs fusion protein.…”
Section: The Locations Of Vhs Cleavage Sites In Truncated Transcriptssupporting
confidence: 78%
See 4 more Smart Citations
“…The results described above were in agreement with the pattern of degradation of IEX-1 mRNA observed in HSV-1-infected cells and specifically with the lingering of truncated 5Ј domains, generated by vhs-dependent endonucleolytic cleavage within the AREs (19,21). The objective of the experiments described in this section was to test whether a substrate, consisting of only IEX-1 coding sequence domain (CDS, substrate 3), was cleaved by the purified GST-vhs fusion protein.…”
Section: The Locations Of Vhs Cleavage Sites In Truncated Transcriptssupporting
confidence: 78%
“…The choice of this specific substrate was based on earlier studies showing that, in infected cells, IEX-1 mRNA was transcribed but that the protein was not made (21). Extensive analyses showed that IEX-1 mRNA was degraded in a unique, vhs-dependent manner (19,21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations